Assessment of the acute toxicity of the organochlorine pesticide endosulfan in Cichlasoma dimerus (Teleostei, Perciformes) - Da Cuña, Rodrigo Hernán (2011)
The organochlorine insecticide endosulfan (ES) is widely used despite its high toxicity to fish (96-h LC50 median value of 2.6γgL-1). This study aimed to assess the acute toxicity, histological and physiological parameters after exposure to 0; 0.25; 1; 2; 3; 4 and 16γgL-1 ES for 96h under semi-static conditions in a freshwater perciform fish, Cichlasoma dimerus. Prior to death, fish exhibited behavior indicative of neurotoxicity. No difference was found in brain AChE activity. A decrease in erythrocyte mean corpuscular volume, mean corpuscular hemoglobin and mean corpuscular hemoglobin concentration in exposed fish suggests a state of anemia. Histological alterations observed in exposed fish included hyperplasia of the interlamellar epithelium, blood congestion in secondary lamellae, and mucous cells hyperplasia and hypertrophy in gills; pycnotic nuclei and hydropic degeneration in liver; testicular damage. These moderate pathological responses in major organs could become crucial during reproduction and under prolonged exposure periods.